2020
DOI: 10.7224/1537-2073.2018-036
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Activity Participation After Multiple Sclerosis Diagnosis

Abstract: Background: Multiple sclerosis (MS) results in impairments in cognitive and motor skills, which may reduce the level of activity participation in people with MS. This study compares past and current levels of activity participation in adults with MS and controls. The relationship between retained activity participation (since diagnosis) and cognitive, motor, functional status, and depression symptoms of persons with MS was examined. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…walking, manual dexterity and cognition) over decades. 47 In fact, reduced ability to engage in activities that comprise a certain degree of complexity regarding initiative and planning is common even in PwMS mildly and moderately affected by multiple sclerosis (MS) 8 – varying from 21% in the mild group to 73% in the moderate group – which in turn has a negative impact on quality of life. 8,9 While most previous longitudinal studies have shown restricted participation in complex social/lifestyle activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…walking, manual dexterity and cognition) over decades. 47 In fact, reduced ability to engage in activities that comprise a certain degree of complexity regarding initiative and planning is common even in PwMS mildly and moderately affected by multiple sclerosis (MS) 8 – varying from 21% in the mild group to 73% in the moderate group – which in turn has a negative impact on quality of life. 8,9 While most previous longitudinal studies have shown restricted participation in complex social/lifestyle activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A significant finding of the current study is that more HA were engaged in everyday occupations with and without modifications compared with persons with MS. We were not surprised to find that persons with MS were less engaged than HA in daily occupations during the pandemic. It is known that persons with MS usually experience some levels of restriction in occupations of daily living imposed by symptoms of their disease regardless of the pandemic ( Conradsson et al, 2018 ; Goverover et al, 2020 ). In addition, we found that changes in daily occupations were made by both groups in most activities, however, HA used more modifications than MS to maintain engagement.…”
Section: Discussionmentioning
confidence: 99%
“…MS affects up to a million people in the United States ( Wallin et al, 2019 ) and often results in limitations and restrictions in occupations of daily living ( Goverover et al, 2015 , 2020) and a reduced HrQOL ( Goverover et al, 2020 ). The challenges imposed by the pandemic may have had an additive negative effect on various aspects of life for individuals with MS.…”
Section: Introductionmentioning
confidence: 99%
“…Processing speed is a fundamental cognitive function that underlies other cognitive processes, such as memory and executive functions (Costa, Genova, DeLuca, & Chiaravalloti, 2017). The role of cognition in activity performance, including IBT use, is of particular concern for persons with MS, for whom cognitive deficits are common (Chiaravalloti & DeLuca, 2008; Goverover et al, 2020). For technology design and training, processing-speed issues should be considered to improve the actual capabilities of persons with MS to use IBT.…”
Section: Discussionmentioning
confidence: 99%
“…MS most commonly follows a relapsing–remitting disease course, which affects 85% of those diagnosed (Hersch & Fox, 2018). Symptoms are usually chronic and progressive, with individuals experiencing disability in the form of impaired everyday activities and limited social participation (Goverover & DeLuca, 2018; Goverover, Genova, Smith, Lengenfelder, & Chiaravalloti, 2020).…”
mentioning
confidence: 99%